2 x 2 + y 2 2 x 4 + 4 y 4 + 9
If x and y non-zero real numbers such that their product is 1, find the minimum value of the expression above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
First is to factor left hand side
2 x 4 + 4 y 4 + 9 = ( 2 x 2 + y 2 ) ( 4 y 2 + x 2 )
So,
2 x 2 + y 2 2 x 4 + 4 y 4 + 9 = 4 y 2 + x 2 Since x and y aren't equal to 0.
use x = y 1
then we have
4 y 2 + y 2 1 and we have to find the minimum of this funtion.
Since the derivative must equal to 0.
8 y − y 3 2 = 0 then y 4 = 4 1 , y 2 = 2 1
Hence
4 y 2 + y 2 1 = 2 + 2 = 4
Great solution. I was hoping there would be a calculus method :)
Also, note that you could of used AM-GM to minimize 4 y 2 + y 2 1 as y 2 > 0
A different solution:
The minimum of the expression is the greatest k such that
2 x 2 + y 2 2 x 4 + 4 y 4 + 9 ≥ k
for all nonzero x,y such that x y = 1. Re-arranging, we must have that
2 1 ( x 2 − 2 k ) 2 + ( y 2 − 8 k ) 2 ≥ 4 1 ( 1 6 9 k 2 − 9 )
Note that if − 4 < k < 4 then the above inequality is true for all x,y. Hence, k>=4.
Suppose k>4. Then we cannot find x,y with xy=1 so that the expression equals 4. However, if (x,y)=(sqrt(2),1/sqrt(2)), then the expressin equals 4. Hence, we have a contradiction. So k=4.
Using Cauchy-Schwartz Inequality and then AM-GM inequality, ( 2 + 4 1 + 4 9 ) ( 2 x 2 + y 2 2 x 4 + 4 y 4 + 9 ) ≥ 2 x 2 + y 2 ( 2 x 2 + y 2 + 2 9 ) 2 = 9 + ( 2 x 2 + y 2 ) + 4 ( 2 x 2 + y 2 ) 8 1 ≥ 9 + 2 ( 2 9 ) = 1 8
Hence, 2 x 2 + y 2 2 x 4 + 4 y 4 + 9 ≥ 1 8 × 9 2 = 4
The equality holds if and only if 2 2 x 4 = 4 1 4 y 4 = 4 9 9 and 2 x 2 + y 2 = 2 9 . It is possible if ( x , y ) = ( 2 , 2 1 ) .
I saw this question again and tried it using the following method: 2 x 2 + y 2 2 x 4 + 4 y 4 + 9 = 2 x 2 + x 2 1 2 x 4 + x 4 4 + 9 = ( 2 x 4 + 1 ) x 2 2 x 8 + 9 x 4 + 4 = ( 2 x 4 + 1 ) x 2 x 4 ( 2 x 4 + 1 ) + 4 ( 2 x 4 + 1 ) = x 2 + x 2 4 ≥ 2 4 = 4
Let 2 x 2 + y 2 2 x 4 + 4 y 4 + 9 ≥ C using xy = 1 (to make the inequality homogeneous) and rearranging ⇒ 2 x 4 + 4 y 4 + 9 x 2 y 2 ≥ C ( 2 x 2 + y 2 ) Factorising the LHS: ( 2 x 2 + y 2 ) ( x 2 + 4 y 2 ) ≥ C ( 2 x 2 + y 2 ) ( 2 x 2 + y 2 ) ( 4 y 2 + x 2 − C ) ≥ 0 Using xy = 1 again: ( 2 x 2 + y 2 ) ( 4 y 2 + x 2 − C x y ) ≥ 0 Now we need the 2nd bracket to be a square... 4 y 2 + x 2 − C x y ≡ ( a − b ) 2 ⇒ ( 4 y 2 + x 2 − C x y ) = ( 2 y − x ) 2 ∴ M i n V a l u e = C = 4 This is achieved when x = 2 y ⇒ x y = 2 y 2 = 1 ⇒ y = ± 2 2 a n d x = ± 2
Problem Loading...
Note Loading...
Set Loading...
2 x 2 + y 2 2 x 4 + 4 y 4 + 9 = 2 x 2 + y 2 2 x 4 + 9 x 2 y 2 + 4 y 4 [ x y = 1 ] = 2 x 2 + y 2 ( 2 x 2 + y 2 ) ( x 2 + 4 y 2 ) = x 2 + 4 y 2 ≥ 2 4 x 2 y 2 = 4 x y = 4 [ A M ≥ G M ]